Attempt at taxonomical characterization of some Rhizobial species by intact cell MALDI mass spectrometry - Prabhu, R. R.; Kulkarni, Mahesh J.; Parasharami, V. A.; Santhakumari, B.; Paranjape, S. (World Journal of Microbiology & Biotechnology, 2007)
In the present study an attempt was made to exploit the benefit of intact cell MALDI mass spectrometry (ICM-MS) in bringing out similarities and differences among some Rhizobium species and a species of Agrobacterium based on specific mass:charge (m/z) values. Rhizobium species isolated from the root nodules of selected leguminous plants were analysed by ICM-MS. The spectra were acquired in the range of 500-10,000 Da yielding several peaks specific to each species. The peaks obtained corresponded to the respective bacterial cell surface molecules which were desorbed during matrix-assisted laser desorption ionization. The number of peaks were more in the range of 500-1200 Da. Dice similarity coefficient analysis of m/z values indicated that Rhizobium species isolated from Trigonella foenum-graecum and Pisum arvense showed more similarity than any other species. Agrobacterium species did show a few common m/z values in comparison with other Rhizobium species. This clearly shows that Agrobacterium is closely related to Rhizobium. Eventually, ICM-MS technique offers clear, distinct, and consistent results for replicates, in less than an hour's time, therefore this technique has high potential in molecular taxonomy.
Keywords: ICM-MS; legume; molecular taxonomy; Rhizobium; symbiotic

Application of a stability-indicating thin-layer chromatographic method to the determination of tenatoprazole in pharmaceutical dosage forms - Dhaneshwar, Sunil R.; Bhusari, Vidhya K.; Mahadik, Mahadeo V.; Santhakumari, B. (Journal of AOAC International, 2009)
A sensitive, selective, precise, and stability-indicating thin-layer chromatographic (TLC) method was developed and validated for the determination of tenatoprazole both as a bulk drug and in formulation. The method uses TLC aluminum plates precoated with Silica Gel 60(F-254) as the stationary phase and the solvent system toluene-ethyl acetate-methanol (6 + 4 + 1, v/v/v). This system gave compact spots for tenatoprazole (R(f) value of 0.34 +/- 0.02). Tenatoprazole was subjected to acid and alkali hydrolysis, oxidation, and photodegradation. The peaks of the degradation products were well-resolved from that of the pure drug and had significantly different Rf values. Densitometric analysis of tenatoprazole was performed in the absorbance mode at 306 nm. The linear regression analysis data for the calibration plots showed a good linear relationship over the concentration range of 100-1500 ng/spot. The mean values of the correlation coefficient, slope, and intercept were 0.9989 +/- 1.42, 10.27 +/- 0.965, and 4894.2 +/- 1.24, respectively. The method was validated for precision, robustness, and recovery. The limit of detection and limit of quantitation were 50 and 100 ng/spot, respectively. Statistical analysis showed that the method is repeatable and selective for estimation of tenatoprazole. Because the method can separate the drug from its degradation products, it can be used to monitor stability.

Analytical and bioanalytical UHPLC-MS method validation for determination of metformin, a bigunaide and sitagliptin, a DPP-4 inhibitor - Nakrani, Mital; Bairagee, Deepika; Goyal, Pradeep; Santhakumari, B. (International Journal of Pharmacy and Pharmaceutical Sciences, 2015)